Optimal design of solar/wind/battery and EV fed UPQC for power quality and power flow management using enhanced most valuable player algorithm - Srilakshmi, Koganti; Gaddameedhi, Sravanthy; Borra, Subba Reddy; Balachandran, Praveen Kumar; Reddy, Ganesh Prasad; Palanivelu, Aravindhababu; Selvarajan, Shitharth (Frontiers in Energy Research, 2024)
The behavior and performance of distribution systems have been significantly impacted by the presence of solar and wind based renewable energy sources (RES) and battery energy storage systems (BESS) based electric vehicle (EV) charging stations. This work designs the Unified Power Quality Conditioner (UPQC) through optimal selection of the active filter and PID Controller (PIDC) parameters using the enhanced most valuable player algorithm (EMVPA). The prime objective is to effectively address the power quality (PQ) challenges such as voltage distortions and total harmonic distortions (THD) of a distribution system integrated with UPQC, solar, wind, BESS and EV (U-SWBEV). The study also aims to manage the power flow between the RES, grid, EV, BESS, and consumer loads by artificial neuro-fuzzy interface system (ANFIS). Besides, this integration helps to have a reliable supply of electricity, efficient utilization of generated power, and effective fulfillment of the demand. The proposed scheme results in a THD of 4.5%, 2.26%, 4.09% and 3.98% for selected four distinct case studies with power factor to almost unity with an appropriate power sharing. Therefore, the study and results indicate that the ANFIS based power flow management with optimal design of UPQC addresses the PQ challenges and achieves the appropriate and effective sharing of power.